Developing teacher professionalism through scientific writing - Supriyadi, Supriyadi (Technium Social Sciences Journal, 2022)
Professional teachers have four competencies, namely (a) pedagogical competence, (b) cognitive competence, (c) personality competence, and (d) social competence. Among these competencies, learning management is the one we most emphasize. That is, professional teachers must be able to develop learning programs, choose and use learning media and appropriate strategies. Professional teachers must be able to communicate effectively that can motivate their students. They must also have extensive knowledge in their disciplines, be wise, and be well-socialized. The teaching profession is a special field of work that requires professional principles. Professional teachers are those with the competencies required to carry out education and learning duties. Regarding this, writing a scientific paper is one form of activity that can develop teacher professionalism. It should be emphasized that scientific writing is the most substantial activity in developing teacher professionalism. Compiling a scientific paper for teachers is a basic requirement to develop their profession. This is because teachers are considered (a) educated people, (b) reformers in the field of education, (c) motivators, and partners for students, and (d) role models for students in writing scientific paper, (e) researchers in the field of learning, and (f) writers of scientific papers.Professional teachers have four competencies, namely (a) pedagogical competence, (b) cognitive competence, (c) personality competence, and (d) social competence. Among these competencies, learning management is the one we most emphasize. That is, professional teachers must be able to develop learning programs, choose and use learning media and appropriate strategies. Professional teachers must be able to communicate effectively that can motivate their students. They must also have extensive knowledge in their disciplines, be wise, and be well-socialized. The teaching profession is a special field of work that requires professional principles. Professional teachers are those with the competencies required to carry out education and learning duties. Regarding this, writing a scientific paper is one form of activity that can develop teacher professionalism. It should be emphasized that scientific writing is the most substantial activity in developing teacher professionalism. Compiling a scientific paper for teachers is a basic requirement to develop their profession. This is because teachers are considered (a) educated people, (b) reformers in the field of education, (c) motivators, and partners for students, and (d) role models for students in writing scientific paper, (e) researchers in the field of learning, and (f) writers of scientific papers.